Internalisasi Pendidikan Karakter Pada Anak Usia Dini Dalam Keluarga Hindu Di Desa Timpag Kabupaten Tabanan - I Made Gami Sandi Untara; Ayu Veronika Somawati (Cetta: Jurnal Ilmu Pendidikan, 2020)
This study aims to determine the internalization of character education in early childhood in Hindu families in the village of Timpag, Kerambitan District, Tabanan Regency. Talking about child psychology is talking about how to educate children right from an early age. Because early childhood has potential that still needs to be developed and has certain characteristics that are unique and not the same as adults, they are always active, dynamic, enthusiastic and curious about what they see, hear, feel, as if they never stop explore and learn. The method used in this research is qualitative with descriptive research type. Primary data sources were obtained by interviewing informants, secondary data sources were obtained from literature, literature and documentation studies. Based on the results of research on internalization of character education in early childhood in a Hindu family in the village of Timpag is by a) Formation of the character of children in a Hindu family by building a family without violence is one effective solution to make a child feel comfortable, peaceful, peaceful at home, b) Early childhood care patterns in the family by building children's attitudes including training children to have a bold attitude, honest and other attitudes, build emotions of children who are not easily angry, quarreling, lazy and so on. Building the intelligence and will of the child to build communication between children and fellow children and parents, c) Understanding the psychology of children as a key understanding of education related to mental development and personality of the child, after physical needs are met-fulfilled then the child's needs will increase towards social needs and love obtained through interaction, both with parents (family) community and at school, d) Parents as educators and must send their children to school because the successful role of parents as educators is the formation of children who are nimble, clever, empowered good effort.